2014
DOI: 10.3389/fnhum.2013.00935
|View full text |Cite
|
Sign up to set email alerts
|

Mental workload during n-back task—quantified in the prefrontal cortex using fNIRS

Abstract: When interacting with technical systems, users experience mental workload. Particularly in multitasking scenarios (e.g., interacting with the car navigation system while driving) it is desired to not distract the users from their primary task. For such purposes, human-machine interfaces (HCIs) are desirable which continuously monitor the users' workload and dynamically adapt the behavior of the interface to the measured workload. While memory tasks have been shown to elicit hemodynamic responses in the brain w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
214
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(259 citation statements)
references
References 36 publications
28
214
1
Order By: Relevance
“…In order to examine whether fNIRS is equipped with necessary sensitivity as a potential alternative of fMRI, they investigate the sensitivity to detecting linear changes in activation and functional connectivity in response to cognitive load, and functional connectivity changes when transitioning from a task-free resting state to a task performance (a letter n-back task with three load conditions). The results demonstrate that fNIRS is sensitive to both cognitive load and state (Herff et al, 2014). Interesting, almost identical findings are reported by another group of scientists (Fishburn et al, 2014).…”
supporting
confidence: 85%
“…In order to examine whether fNIRS is equipped with necessary sensitivity as a potential alternative of fMRI, they investigate the sensitivity to detecting linear changes in activation and functional connectivity in response to cognitive load, and functional connectivity changes when transitioning from a task-free resting state to a task performance (a letter n-back task with three load conditions). The results demonstrate that fNIRS is sensitive to both cognitive load and state (Herff et al, 2014). Interesting, almost identical findings are reported by another group of scientists (Fishburn et al, 2014).…”
supporting
confidence: 85%
“…The stimuli viewing task was passive, possibly involving bottom-up processing, whereas the visual attention task was more demanding and required additional top-down processing. Previous research utilizing fNIRS has shown increases in PFC oxy-Hb activity as a cognitive task gets progressively more difficult [32,33]. Despite these differences in oxy-Hb between our two tasks no influence of emotion on PFC oxy-Hb activity was observed.…”
Section: Channelcontrasting
confidence: 37%
“…This finding suggests such interactions may be evident in brain regions involved in cognitive control as changes in dlPFC activity in response to threat distractors differ according to task difficulty. It has also been shown that PFC oxy-Hb activity increases as a cognitive task becomes more demanding [32,33]. It is possible that as the current study only adopted one level of task difficulty the task may have been too demanding and therefore masked any possible influence of emotion on PFC oxy-Hb activation.…”
Section: Channelmentioning
confidence: 76%
“…Many NIRS studies have adopted an n -back paradigm to study neural processing during WM performance in healthy individuals [48,49,50] and in those with schizophrenia [51], major depression disorder [52], or attention-deficit/hyperactivity disorder [53]. These studies have consistently reported that healthy individuals exhibit increased frontal activations indicated by [oxy-Hb] increases, especially in the VLPFC and DLPFC when responding to an increase in WM load [48,49,50,51]. These findings are consistent with those reported in the fMRI literature [24] and support the use of NIRS to understand neural processing during WM tasks.…”
Section: Introductionmentioning
confidence: 99%